The great bear conflab - Wignell, Edel; Madder, Sharyn (Macmillan Education Australia South Yarra [Vic.], 1999)
Great Bear Conflab is a captivating children's book that tells the story of a group of bears who gather to discuss important matters in their forest home. Through engaging narratives and delightful illustrations, the book explores themes of friendship, teamwork, and problem-solving. As the bears share their thoughts and ideas, young readers are encouraged to think critically and appreciate the value of communication and cooperation. This charming tale fosters a love for storytelling while imparting important life lessons in a fun and relatable way.